Cardiovascular risk factors and sociodemographic characteristics in elderly registered in a Family Health Unit - de Jesus Bispo, Inaê Mariane; Silva Santos, Patrícia Honório; Oliveira Carneiro, Maria Aldenice; Borges Santana, Tamiles Daiane; Fernandes, Marcos Henrique; Casotti, Cesar Augusto; Santana Cardoso Santos, Isleide; Oliveira Carneiro, José Ailton (O Mundo da Saúde, 2016)
Population aging is accompanied by changes in the pattern of morbidity and mortality, resulting in increased exposure of individuals to the risk factors and noncommunicable chronic diseases. This study aimed to identify the prevalence of modifiable cardiovascular risk factors and to associate with the sociodemographic characteristics of elderly registered in a Family Health Unit. This is an observational cross-sectional study, conducted with 139 elderly people. Data collection was carried out through a structured questionnaire containing questions regarding sociodemographic information and cardiovascular risk factors (smoking, alcoholism, hypertension, diabetes, sedentary and overweight/obesity). Anthropometric measurements also were realized, such as weight, height and abdominal circumference, the body mass index also was calculated. It was observed that of the 139 recruited elderly, 75.5% were female. The mean age of the elderly was 72.32 ± 8.4 years. The prevalence of cardiovascular risk factors were: hypertension 64.7%; obesity 63.1%; sedentary lifestyle 46.8%; abdominal circumference high 41.3%, diabetes mellitus 15.1%; alcoholism 13.8% and smoking 10.1%. Association was verified between sedentary and age group of 60-69 years (p=0.004) and non-caucasians/race (p=0.013); high abdominal circumference (p=0.005) and smoking (p = 0.03) with female sex; consumption of alcohol with males (p=0.004) and diabetes mellitus with economic class A and B (p = 0.04). This study showed a high prevalence of cardiovascular risk factors in elderly registered in a Family Health Unit.